ABCDEF Bundle Practices for Critically Ill Children: An International Survey of 161 PICUs in 18 Countries*. Issue 1 (13th July 2021) - Ista, Erwin; Redivo, Juliana; Kananur, Paurav; Choong, Karen; Colleti, Jose; Needham, Dale M.; Awojoodu, Ronke; Kudchadkar, Sapna R.; ,
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To evaluate current international practice in PICUs regarding components of the "Assessing Pain, Both Spontaneous Awakening and Breathing Trials, Choice of Sedation, Delirium Monitoring/Management, Early Exercise/Mobility, and Family Engagement/Empowerment" (ABCDEF) bundle. Design: Online surveys conducted between 2017 and 2019. Setting: One-hundred sixty-one PICUs across the United States ( n = 82), Canada ( n = 14), Brazil ( n = 27), and Europe ( n = 38) participating in the Prevalence of Acute Rehabilitation for Kids in the PICU study. Interventions: None. Measurements and Main Results: Of the 161 participating PICUs, 83% were in academic teaching hospitals and 42% were in free-standing children's hospitals. Median size was 16 beds (interquartile range, 10–24 beds). Only 15 PICUs (9%) had incorporated all six ABCDEF bundle components into routine practice. Standardized pain assessment (A) was the most common (91%), followed by family engagement (F, 88%) and routine sedation assessment (C) with validated scales (84%). Protocols for testing extubation readiness or conducting spontaneous breathing trials (B) were reported in 57%, with 34% reporting a ventilator weaning protocol. Routine delirium monitoring with a validated screening tool (D) was reported by 44% of PICUs, and 26% had a guideline, protocol, or policy for early exercise/mobility (E). Practices for spontaneous breathing trials were variable in 29% of Canadian PICUs versus greater than 50% in the other regions. Delirium monitoring was lowest in Brazilian PICUs (18%) versus greater than 40% in other regions, and family engagement was reported in 55% of European PICUs versus greater than 90% in other regions. Conclusions: ABCDEF bundle components have been adopted with substantial variability across regions. Additional research must rigorously evaluate the efficacy of specific elements with a focus on B, D, E, and full ABCDEF bundle implementation. Implementation science is needed to facilitate an understanding of the barriers to ABCDEF implementation and sustainability with a focus on specific cultural and regional differences.